The Post-Movement Beta Rebound and Motor-Related Mu Suppression in Children. Issue 5 (2nd September 2020) - Hao, Junyi; Feng, Wenfeng; Zhang, Lingli; Liao, Yu
Abstract: Age-related EEG activity change is a prominent feature that reflects the functional development of the brain. The current study investigated the beta and mu rhythms of 16 children (7.7 ± 1.5 years, 5 to 9.6 years) and 13 adults when a self-determining arm motion was performed. The results indicated that mu power was decreased during movement and returned to baseline level after the movement for both children and adults. However, although a decrease in beta power was observed for both children and adults during movement, the post-movement beta power rebound (PMBR) was observed in adults but not in children. These results suggest that motor-related mu suppression develops early in children; PMBR develops later and may be associated with a more prolonged motor development process.